IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) DALAM PENINGKATAN MUTU MADRASAH ALIYAH - Agus Dian Alirahman; Shulkhah Shulkhah; Ali Nuruddin Nurul Ilmi (Universitas Islam Bunga Bangsa Cirebon, 2022)
The quality of Islamic secondary education (Madrasah Aliyah) in Indonesia remains a central concern amid growing demands for competitive and character-based graduates. This study examines the implementation of Total Quality Management (TQM) as a strategic framework for improving educational quality in Madrasah Aliyah. The primary objective is to analyze how TQM principles encompassing continuous improvement, customer focus, data-driven decision-making, and stakeholder involvement are operationalized within the madrasah context. Employing a systematic library research methodology, this study collects, reviews, and synthesizes data from peer-reviewed journal articles, authoritative books, and official educational policy documents published within the last five years. Thematic and content analysis techniques were applied to identify patterns and draw comprehensive conclusions. Findings indicate that madrasahs implementing TQM systematically demonstrate measurable improvements in academic performance, institutional governance, teacher professionalism, and stakeholder satisfaction. However, significant gaps remain in leadership commitment, resource allocation, and monitoring mechanisms. This study contributes to the theoretical and practical discourse of Islamic educational management by offering evidence-based recommendations for TQM adoption in madrasah environments.